Generation and Characterisation of a Pax8-CreERT2 Transgenic Line and a Slc22a6-CreERT2 Knock-In Line for Inducible and Specific Genetic Manipulation of Renal Tubular Epithelial Cells. - Judit Espana-Agusti; Xiangang Zou; Kim Wong; Beiyuan Fu; Fengtang Yang; David A Tuveson; David J Adams; Athena Matakidou (PLoS ONE)
Genetically relevant mouse models need to recapitulate the hallmarks of human disease by permitting spatiotemporal gene targeting. This is especially important for replicating the biology of complex diseases like cancer, where genetic events occur in a sporadic fashion within developed somatic tissues. Though a number of renal tubule targeting mouse lines have been developed their utility for the study of renal disease is limited by lack of inducibility and specificity. In this study we describe the generation and characterisation of two novel mouse lines directing CreERT2 expression to renal tubular epithelia. The Pax8-CreERT2 transgenic line uses the mouse Pax8 promoter to direct expression of CreERT2 to all renal tubular compartments (proximal and distal tubules as well as collecting ducts) whilst the Slc22a6-CreERT2 knock-in line utilises the endogenous mouse Slc22a6 locus to specifically target the epithelium of proximal renal tubules. Both lines show high organ and tissue specificity with no extrarenal activity detected. To establish the utility of these lines for the study of renal cancer biology, Pax8-CreERT2 and Slc22a6-CreERT2 mice were crossed to conditional Vhl knockout mice to induce long-term renal tubule specific Vhl deletion. These models exhibited renal specific activation of the hypoxia inducible factor pathway (a VHL target). Our results establish Pax8-CreERT2 and Slc22a6-CreERT2 mice as valuable tools for the investigation and modelling of complex renal biology and disease.